(untitled) (Acta Education, 2025)
In this article, the author discusses the basic principles of a systematic approach to the organization of educational activities of a hospital school. In conditions where the educational process is integrated into the conditions of a medical institution, a systematic approach allows for the integrity, adaptability and flexibility of the learning environment. The author highlights the basic principles of the systemic approach, reveals them, showing the relationship with the educational and medical process.